Income and Expanse Account in Forestry - Danusevičienė, Pranciška; Mizaras, Stasys (Ekonomika, 1998)
Activities in forestry are specific, for forest is both a product obtained in the process of growing and a capital providing income. Investments in forestry yield profit only after many years. Besides, profit in forestry is not always expressible by economic indices, because forest has not only economy, but also ecological and social significance. However, under the conditions of market economy all resources have to be used in a most effective way. Managing personnel should be aware of the efficiency of resources they own. Proper management is impossible without adequate knowledge on income and expenses in order to obtain this income. This information should be registered in primary and book - keeping documentation. To make it valid and comparable among separate enterprises, a standard account methodics is suggested. The main accounting principles were set by the Accounting Law (1992). However, each activity its specific sides. Activities in forestry deal not only with utilizing resources to yield income, but also with the recreation, growing and protection of these resources. Therefore, accounting should provide information not only on income and expenses, but also on costs for certain forest management measures. Most silvicultural measures are not strictly separated, thus a methodical agreement is needed to account for expenditure on them. Production is also very diverse and its grouping should be uniform in all forest enterprises. The paper discuses the structure of income and expenses and suggests their grouping model.